Gut microbiome is associated with metabolic syndrome accompanied by elevated gamma-glutamyl transpeptidase in men - Shifeng Sheng; Su Yan; Su Yan; Jingfeng Chen; Yuheng Zhang; Youxiang Wang; Youxiang Wang; Qian Qin; Weikang Li; Tiantian Li; Meng Huang; Suying Ding; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
It is predicted that by 2035, metabolic syndrome (MS) will be found in nearly more than half of our adult population, seriously affecting the health of our body. MS is usually accompanied by the occurrence of abnormal liver enzymes, such as elevated gamma-glutamyl transpeptidase (GGT). More and more studies have shown that the gut microbiota is involved in MS; however, the correlation between gut microbiota and MS with elevated GGT has not been studied comprehensively. Especially, there are few reports about its role in the physical examination of the population of men with MS and elevated GGT. By using the whole-genome shotgun sequencing technology, we conducted a genome-wide association study of the gut microbiome in 66 participants diagnosed as having MS accompanied by high levels of GGT (case group) and 66 participants with only MS and normal GGT level (control group). We found that the number of gut microbial species was reduced in participants in the case group compared to that of the control group. The overall microbial composition between the two groups is of significant difference. The gut microbiota in the case group is characterized by increased levels of “harmful bacteria” such as Megamonas hypermegale, Megamonas funiformis, Megamonas unclassified, Klebsiella pneumoniae, and Fusobacterium mortiferum and decreased levels of “beneficial bacteria” such as Faecalibacterium prausnitzii, Eubacterium eligens, Bifidobacterium longum, Bifidobacterium pseudocatenulatum, Bacteroides dorei, and Alistipes putredinis. Moreover, the pathways of POLYAMSYN-PWY, ARG+POLYAMINE-SYN, PWY-6305, and GOLPDLCAT-PWY were also increased in the case group, which may play a role in the elevation of GGT by producing amine, polyamine, putrescine, and endogenous alcohol. Taken together, there are apparent changes in the composition of the gut microbiome in men with MS and abnormal GGT levels, and it is high time to discover specific gut microbiome as a potential therapeutic target in that population. More in-depth studies of relevant mechanism could offer some new methods for the treatment of MS with elevated GGT.